A Nonlinear Mixed Effects Pharmacokinetic Model for Dapagliflozin and Dapagliflozin 3‐O‐glucuronide in Renal or Hepatic Impairment. (8th May 2013) - van der Walt, J‐S; Hong, Y; Zhang, L; Pfister, M; Boulton, DW; Karlsson, MO
Abstract : Dapagliflozin is a sodium–glucose co‐transporter 2 inhibitor in development for the treatment of type 2 diabetes mellitus. A semi‐mechanistic population pharmacokinetic (PK) model was developed for dapagliflozin and its inactive metabolite dapagliflozin 3‐ O ‐glucuronide (D3OG) with emphasis on renal and hepatic contribution to dapagliflozin metabolism. Renal and hepatic impairment decreased the clearance of dapagliflozin to D3OG and the clearance of D3OG. The fraction of D3OG formed via the renal route decreased from 40–55% in subjects with normal renal function (creatinine clearance (CLcr) > 80 ml/min) to 10% in subjects with severe renal insufficiency (CLcr = 13 ml/min). The model‐based simulations suggested that the increase of systemic exposure (AUCss ) of dapagliflozin and D3OG was less than twofold in subjects with mild or moderate renal impairment. This population modeling analysis presents a useful approach to evaluate the impact of renal and hepatic function on the PK of dapagliflozin. CPT: Pharmacometrics & Systems Pharmacology (2013) 2, e42; doi:10.1038/psp.2013.20 ; advance online publication 8 May 2013